ANALISIS PENGARUH PUBLIKASI LAPORAN KEUANGAN INTERIM TERHADAP ABNORMAL RETURN SAHAM DI BURSA EFEK INDONESIA (BEI) - jatiningrum, citrawati (Jurnal Manajemen dan Keuangan, 2009)
Target of financial statement is provide the information which is concerning financial position of an worthwhile company to a large amount of user in economic decision. Interim financial statement represent the financial statement published among annual financial statement, able to be compiled in monthly, quarterly or other period is which less than one year including entire all financial statement component.This research is aim to prove empirically whether what there is influence which significant of between publication of interim financial statement to abnormal return share at industrial multifarious group company ( miscellaneous industry) in Indonesia Stock Exchanges (BEI). Data used in this research is obtained from JSX Monthly Satatistic, what is obtained from Effect Exchange of Jakarta and Center The Data of Capital Market of FE UGM. Technics analyse the data use the quantitative analysis by using paired-sample t test. In this research is writer test its hypothesis use the probability by Î± = 0,05.There is more other factor of dominant perceived by investor compared to by a interim financial statement information, tardy financial statement information accepted by investor, its professionalism do not institute the supporter and profession in capital market, lack of investor attention in assessing information of concerning prospect of an company in have invesment, inexistence of market strength which mirror from at least request to an share.Keyword : Financial Statement, Abnormal Return Share